Religious Tolerance Drives The Progress of Muhammadiyah Da'wah - Prahastiwi, Eka Danik; Suprayitno, Kabul; Wendahayu, Yayan (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
Muhammadiyah proactively seeks to involve all segments of society in various educational and social activities. This approach not only strengthens the basis of tolerance and understanding between religious communities but also helps reduce prejudice and promote peaceful coexistence. Education is one of the most effective tools used by Muhammadiyah to spread the values ​​of tolerance. Schools and universities founded by this organization offer curricula that emphasize the importance of social harmony and diversity. This education is not limited to academic knowledge alone, but also involves extracurricular activities that promote interaction between students from various religious and ethnic backgrounds. The success of this approach can be seen not only from the harmony maintained between religious communities within Muhammadiyah but also from the recognition and appreciation received from the wider community. This proves that religion can be a positive force in a pluralistic society, supporting the idea that tolerance and harmony are the main pillars in building and maintaining a society.